2019
DOI: 10.2147/cia.s170470
|View full text |Cite
|
Sign up to set email alerts
|

<p>Indicators of oral health in older adults with and without the presence of multimorbidity: a cross-sectional study</p>

Abstract: PurposeThe aim of this study was to determine whether there are differences in the distribution of various indicators of oral health among elderly people with and without multimorbidity (ie, two or more chronic diseases).Subjects and methodsA cross-sectional, comparative study was conducted using a sample of Mexican elderly individuals aged ≥60 years. The average age of the cohort was 79.06±9.78 years, and 69.1% were women. The variables indicating oral health were as follows: functional dentition, edentulism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 33 publications
3
27
0
1
Order By: Relevance
“…5,6 In this study, the most prevalent oral diseases were tooth loss (87.7%), followed by periodontal diseases (80%), tooth wear (66%), dental caries (65.3%), and pulp diseases (54%). These findings were in accordance with previous studies [21][22][23] , and tooth loss was the most common dental problem among the elderly. 15,24,25 Oral cancer was not found in this group of patients.…”
Section: Discussionsupporting
confidence: 93%
“…5,6 In this study, the most prevalent oral diseases were tooth loss (87.7%), followed by periodontal diseases (80%), tooth wear (66%), dental caries (65.3%), and pulp diseases (54%). These findings were in accordance with previous studies [21][22][23] , and tooth loss was the most common dental problem among the elderly. 15,24,25 Oral cancer was not found in this group of patients.…”
Section: Discussionsupporting
confidence: 93%
“…Reduced saliva secretion is a common problem in people with chronic diseases [ 25 , 54 ]. Numerous studies have shown that oxidative/nitrosative stress plays a key role in salivary gland hypofunction in the course of systemic diseases [ 14 , 15 , 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our methodology has been partially described elsewhere. [ 11 – 15 ] During recruitment, we informed potential participants of the objectives of our research and of the confidential manner in which their data would be handled. We also explained that they would be free to leave the study at any time.…”
Section: Methodsmentioning
confidence: 99%